2011
DOI: 10.1073/pnas.1013225108
|View full text |Cite
|
Sign up to set email alerts
|

Low-resolution structure of a vesicle disrupting α-synuclein oligomer that accumulates during fibrillation

Abstract: One of the major hallmarks of Parkinson disease is aggregation of the protein α-synuclein (αSN). Aggregate cytotoxicity has been linked to an oligomeric species formed at early stages in the aggregation process. Here we follow the fibrillation process of αSN in solution over time using small angle X-ray scattering and resolve four major coexisting species in the fibrillation process, namely monomer, dimer, fibril and an oligomer. By ab initio modeling to fit the data, we obtain a low-resolution structure of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
269
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 227 publications
(305 citation statements)
references
References 39 publications
33
269
2
1
Order By: Relevance
“…Hence, the differences between WT and A30P aSN fibrils detected by Nielsen et al [47], suggesting increased β-sheet pairing distances in A30P fibrils and their more compact interfibrillar arrangement, cannot be evidenced in our experimental set-up, neither the use of a single helix form factor newly adopted to analyse lysozyme amyloid aggregates [48] is suitable for our SAXS curves. In agreement with Atomic Force Microscopy results [49], we have considered that 5 the cylinder radius could be polydisperse, and fibril electron density could be different from the one of globular protein, due to the hypothesis of the presence of internal cavities [50,51]. Due to the moderately low sample concentration, to the high aggregation number of amyloid fibrils that determines a low number density of scattering particles in solution, to the lowest available Q value and to the absence of interaction peaks in our SAXS curves, the interactions between fibrils have been neglected.…”
Section: Saxssupporting
confidence: 53%
“…Hence, the differences between WT and A30P aSN fibrils detected by Nielsen et al [47], suggesting increased β-sheet pairing distances in A30P fibrils and their more compact interfibrillar arrangement, cannot be evidenced in our experimental set-up, neither the use of a single helix form factor newly adopted to analyse lysozyme amyloid aggregates [48] is suitable for our SAXS curves. In agreement with Atomic Force Microscopy results [49], we have considered that 5 the cylinder radius could be polydisperse, and fibril electron density could be different from the one of globular protein, due to the hypothesis of the presence of internal cavities [50,51]. Due to the moderately low sample concentration, to the high aggregation number of amyloid fibrils that determines a low number density of scattering particles in solution, to the lowest available Q value and to the absence of interaction peaks in our SAXS curves, the interactions between fibrils have been neglected.…”
Section: Saxssupporting
confidence: 53%
“…It has been proposed that amyloid fibrils of different proteins, including α-synuclein (23,24), can grow most efficiently by the addition of oligomers to the fibril ends. In our experiments we used α-synuclein isolated by gel filtration whose CD spectrum is completely consistent with an unfolded monomeric protein (SI Appendix, section 3).…”
Section: Resultsmentioning
confidence: 99%
“…Growing evidence suggests that soluble oligomeric forms of α-syn, which precede amyloid formation, are causative triggers for the dopaminergic cell loss occurring in PD [4,5]. The morphology and associated mode of toxicity displayed by alternative types of α-syn oligomers are largely dependent on the environmental conditions under which they have been prepared [6][7][8][9][10][11]. Numerous in vitro and in vivo studies on α-syn oligomers have demonstrated that a toxic gain-offunction occurs in the disease state via two main mechanisms: (i) Ca 2 + imbalances caused by the formation of pore-like complexes within lipid membranes, and (ii) transmembrane seeding that then results in intracellular aggregation [1].…”
Section: Introductionmentioning
confidence: 99%